Pharmacologic Considerations for Antimicrobials and Anticoagulants after Burn Injury - Pranav Ravichandran; Kaitlin A. Pruskowski (MDPI AG, 2023)
Derangements in pharmacokinetics and pharmacodynamics (PK/PD) of burn patients are poorly understood and lacking consistent data. This leads to an absence of consensus regarding pharmacologic management of burn patients, complicating their care. In order to effectively manage burn critical illness, knowledge of pharmacologic parameters and their changes is necessary. It is also imperative that the clinician understands how these changes will affect drug dosing. A common practice is to increase antibiotic dosing and/or frequency; however, this may not be necessary and doses should be adjusted to patient- and drug-specific parameters. Additionally, monitoring assays for antibiotic levels as well as coagulation factors can be useful for adjusting dosages to best treat the patient. This review focuses on alterations in PK/PD as well as other physiologic changes after burn injury, with special reference to care in military and austere settings.